(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the activities related to seed breeding as a priority direction in developed countries around the world. It addresses the pressing research issues of preserving the best existing varieties of crops for the long term and utilizing them, as well as creating new varieties through selection.